Beyond basicity: discovery of nonbasic DENV-2 protease inhibitors with potent activity in cell culture - Kühl, Nikos; Leuthold, Mila; Behnam, Mira A. M.; Klein, Christian D. (Journal of medicinal chemistry, 2021)
The viral serine protease NS2B-NS3 is one of the promising targets for drug discovery against dengue virus and other flaviviruses. The molecular recognition preferences of the protease favor basic, positively charged moieties as substrates and inhibitors, which leads to pharmacokinetic liabilities and off-target interactions with host proteases such as thrombin. We here present the results of efforts that were aimed specifically at the discovery and development of noncharged, small-molecular inhibitors of the flaviviral proteases. A key factor in the discovery of these compounds was a cellular reporter gene assay for the dengue protease, the DENV2proHeLa system. Extensive structure-activity relationship explorations resulted in novel benzamide derivatives with submicromolar activities in viral replication assays (EC50 0.24 μM), selectivity against off-target proteases, and negligible cytotoxicity. This structural class has increased drug-likeness compared to most of the previously published active-site-directed flaviviral protease inhibitors and includes promising candidates for further preclinical development.
Gesehen am 16.06.2021